An Econometric Investigation of the Monetary Neutrality and Rationality Propositions from an International Perspective - Hoffman, Dennis L.; Schlagenhauf, Don E. (The Review of Economics and Statistics, 1982)
Dennis L. Hoffman, Don E. Schlagenhauf, An Econometric Investigation of the Monetary Neutrality and Rationality Propositions from an International Perspective, The Review of Economics and Statistics, Vol. 64, No. 4 (Nov., 1982), pp. 562-571